2002
DOI: 10.1143/jjap.41.3572
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nonlinear Elasticity Parameter of Tissues by Ultrasound

Abstract: In this paper, a new parameter that quantifies the intensity of tissue nonlinear elasticity is introduced as the nonlinear elasticity parameter. This parameter is defined based on the empirical information that the nonlinear elastic behavior of soft tissues exhibits an exponential character. To visualize the quantitative nonlinear elasticity parameter, an ultrasonic imaging procedure involving the three-dimensional finite element method (3-D FEM) is presented. Experimental investigations that visualize the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…For instance, the Young's modulus of the tissue phantoms measured in this study is comparable to that reported in [60] (20 to 30 kPa). The Young's modulus of the ex vivo kidney cortex is comparable to results from [61]- [63] (20 to 40 kPa), although higher than results from [64], [65] (7 to 15 kPa). Measurement errors in the Young's modulus reported here may occur because of violations of assumptions in (1), i.e., the medium being isotropic, non-dispersive, and locally homogeneous.…”
Section: Discussionsupporting
confidence: 54%
“…For instance, the Young's modulus of the tissue phantoms measured in this study is comparable to that reported in [60] (20 to 30 kPa). The Young's modulus of the ex vivo kidney cortex is comparable to results from [61]- [63] (20 to 40 kPa), although higher than results from [64], [65] (7 to 15 kPa). Measurement errors in the Young's modulus reported here may occur because of violations of assumptions in (1), i.e., the medium being isotropic, non-dispersive, and locally homogeneous.…”
Section: Discussionsupporting
confidence: 54%
“…Since the 2000s, this focus has shifted to parameters that express the nonlinear material behavior of biological tissues, such as nonlinear elasticity, hyperelasticity and viscoelasticity. Some researchers [6], including Hall et al [7] and Mehrabian et al [8,9], have applied ultrasound and finite element inverse analysis to determine the elastic nonlinearity under large strains (around 10 % axial strain). Additionally, many researchers have reported dynamic multifrequency elastography for viscoelastic imaging using MRI and external oscillation devices [10][11][12].…”
Section: Noninvasive Breast Cancer Diagnosismentioning
confidence: 99%
“…30 Erkamp et al and Nitta and Shiina investigated measurement of the nonlinear relationship between strain and applied stress. 31,32 In the present study, a method for assessing the nonlinear property in the stress-strain relationship of the artery wall was investigated. For this purpose, external cyclic actuation was applied from the skin surface on the brachial artery.…”
Section: Introductionmentioning
confidence: 99%